Português (Anais do Congresso Brasileiro de Processo Coletivo e Cidadania, 2022)
It is extremely important that workers, especially the elderly, who are about to retire, know in advance when their retirement will occur, so that they can plan properly for this new phase. Aiming to fill a gap in the legislation, which generates insecurity and uncertainty in their collective rights, this paper addresses the compulsory retirement of civil servants stabilized by art. 19 of the ADCT. This study aims to provide a comprehensive and critical view of the subject, through the analysis of legislation and jurisprudence, especially labor, which defines that the mandatory retirement age for workers stabilized by the ADCT is 75 years, without forgetting other perspectives arising from medical science, politics and international law.